Factors that influence Malaysian customers' intention to repurchase through online group buying (OGB) - Intan Naquiah Md Noor (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
The aim of this research is to investigate factors that influence Malaysian customer’s intention to repurchase using Online Group Buying (OGB). OGB is an e-commerce platform and it refers to group or collective buying where consumers combine their purchasing power in order to obtain significant volume discounts from retailers. Based on the Technology Acceptance Model (TAM) specifically, this study examines the influence of perceived usefulness and perceived ease of use with the additional variables - price, electronic word of mouth and perceived risk on consumers repurchase intention using OGB. Using survey questionnaire as its main instrument, 200 respondents who have experience using OGB had participated in the survey. Data was analysed using SPSS. The findings show that only perceived ease of use, electronic word of mouth and perceived risk have significant influence on consumers repurchase intention using OGB in the country. These empirical evidences provide insights for practitioners in particular the marketing managers of OGB platforms on how to better strategize in order to attract and sustain the customers.